Ecological Vulnerability of Lake Basin by Integrating Human Activity Indicators based on RS and GIS: A Case of Fuxian Lake in Yunnan Province, China. Issue 1 (July 2021) - Zhou, Jing; Tang, Jinli; Yang, Yanjun; Yang, Hailan; Li, Lan; Wu, Li
Abstract: The variation of landscape pattern and vulnerability can indicate the ecological environmental state. This study established a model for landscape pattern vulnerability based on human activity intensity by taking five sets of land use data (1995, 2000, 2005, 2010 and 2015). Landscape sensitivity index, landscape adaptability index and human activity intensity of land surface were all used to compute the landscape vulnerability index. In virtue of Fragstats 4.2 and ArcGIS 10.5, landscape index can be obtained and spatial-temporal distribution and evolution of landscape pattern vulnerability were analysed. Results showed that, (1) from 1995 to 2015, the human activity intensity and landscape pattern vulnerability in the Fuxian Lake Basin deteriorated gradually, the area of higher intensity/vulnerability and high intensity/vulnerability dramatically expanded with time. (2) the spatial heterogeneity of landscape pattern vulnerability increased, there are significant differences between the north, south ends and east, west sides of Fuxian Lake. (3) The global spatiality of landscape pattern vulnerability exhibited strong positive correlation with the significant form of spatial agglomeration, and the positive spatial autocorrelation continued to keep on but the tendency of spatial concentration was slightly decreasing over time. The local autocorrelation mainly based on high-high accumulation zone and low-low accumulation zone had stronger spatial autocorrelation among neighbouring space units. Due to the implementation of the protection policy, the landscape pattern vulnerability in the east sides of Fuxian Lake had expressed declining trend, but that in the north need more attention and protection.